2017
DOI: 10.1002/ajoc.201700211
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Pictet–Spengler Reaction of Cyclic Iminium ions: A Novel Access to Benzo[1,4]oxazepine‐Fused Tetrahydroisoquinoline and Tetrahydro‐β‐carboline Analogues

Abstract: A simple and efficient approach has been developed for the synthesis of benzo[1,4]oxazepino‐fused tetrahydroisoquinoline and tetrahydro‐β‐carboline derivatives via one‐pot cascade reaction sequence. This reaction involves the intramolecular Pictet–Spengler reaction of cyclic iminium ions, which were generated in situ via trifluoroacetic acid (TFA)‐mediated deprotection of an acetal derived from β‐arylethylamines and 2‐(2,2‐diethoxyethoxy)benzaldehyde. All reactions produced a novel library of complex fused pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The key step of the synthetic route was an intramolecular acidcatalyzed Pictet-Spengler condensation of aldehyde 7, proceeding through the intermediate imine 8 (Figure 2). While intramolecular Pictet-Spengler condensations have been previously reported, [14][15][16] they are typically implemented in the construction of comparatively less strained 1,2-bridged β-carboline and isoquinoline structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key step of the synthetic route was an intramolecular acidcatalyzed Pictet-Spengler condensation of aldehyde 7, proceeding through the intermediate imine 8 (Figure 2). While intramolecular Pictet-Spengler condensations have been previously reported, [14][15][16] they are typically implemented in the construction of comparatively less strained 1,2-bridged β-carboline and isoquinoline structures.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism is presumably similar to the well-reported acyl-iminium Pictet-Spengler condensations often applied in the synthesis of carboline structures. [14,17,18] This modification of reaction conditions would be valuable in cases where further modification of the scaffold is required, removing the need for additional steps to protect the reactive bridging amine.…”
Section: Resultsmentioning
confidence: 99%
“…Again in 2017, Unnava et al reported intramolecular Pictet-Spengler reaction of cyclic iminium ions to access benzo [1,4]oxazepine fused tetrahydroisoquinoline derivatives 512 (Scheme 304). [303] Wang and Studer have reported annulation of αbenzylated tosylmethyl isocyanide 513 in presence of Togni reagent (339) as trifluoromethylating agent. The reaction follows a sequential double α-alkylation strategy (Scheme 305).…”
Section: Non-metal Catalyzed Isoquinoline Synthesis and Other Methodsmentioning
confidence: 99%
“…reported intramolecular Pictet‐Spengler reaction of cyclic iminium ions to access benzo[1,4]oxazepine fused tetrahydroisoquinoline derivatives 512 (Scheme 304). [303] …”
Section: Synthesis Of Isoquinoline Derivativesmentioning
confidence: 99%
“…Here, construction of the tetracyclic framework 1a was effected via an intramolecular Pictet-Spengler reaction of an in situ generated cyclic acyliminium ion derived from 2 to generate racemic derivatives ( Figure 2). [35] We sought to engage a different retrosynthetic approach to the sulfur-containing thiazepino[3,4-a]isoquinoline framework as depicted in Figure 2. Accordingly, the thiazepino framework 1b was anticipated to be synthesized from the tetrahydroisoquinoline alcohol intermediate 5.…”
mentioning
confidence: 99%